Murals of the Chapel in the Village of Vasileva Gora in Torzhoksky District of Tver region: the Problem of European Influence on Church Monumental Painting of the Late 18th century - Surova, Anna A. (Actual Problems of Theory and History of Art, 2025)
The article is dedicated to a unique sample of cult painting of Tver region that has not been studied yet. The aims of the author are to study the history of creation of the chapel’s murals and their stylistic peculiarities, to understand the whole conception and to find its origins.